Pengaruh idealisme, relativisme, love of money, dan tingkat pengetahuan terhadap persepsi mahasiswa atas perilaku tidak etis akuntan - Abiprilia, selly rekha; Tituk Diah Widajantie (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to test and demonstrate the effectiveness of idealism , relativism, love of money, and the level of knowledge on student perceptions of unethical behavior by accountants. This study used a quantitative method with Partial Least Square as an analytical technique. Samples were taken from as many as 114 respondents using the non-probability sampling technique. The data collection technique used is a questionnaire via a google form. The results showed that: 1) The higher the idealism level of students, the lower of committing fraud on accountants' ethical behavior. 2) The high value of relativism indicated that the perceptions expressed by students did not only refer to universal moral values or rules but were also viewed from another side. Therefore, accounting students expressed positive perceptions of unethical behavior by accountants until nowadays. 3) The high love of money factor means that the lower the person's ethical behavior. 4) The more comprehensive the students' knowledge of the accounting profession scandal, the more mishandling it would occur. Hence, the student's perception of the unethical behavior of professional accountants would decrease.